Drug Loaded Biodegradable Load-Bearing Nanocomposites for Damaged Bone Repair; AIP Conference Proceedings; Vol. 1882 : Physics of Cancer: Interdisciplinary Problems and Clinical Applications (PC IPCA’17) - Gutmanas E. Y.; Gotman I.; Sharipova A.; Psakhie S. G. Sergey Grigorievich; Swain S. K.; Unger R. (2017, 2017)
Title screen